Overshadowed by shadowing: Exploring how Canadian medical students experience shadowing - Li, Ming K; Xu, Grace; Veinot, Paula; Mylopoulos, Maria; Law, Marcus (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2023)
Background: Preclinical medical students commonly perceive shadowing as beneficial for career exploration. However, research is sparse on the broader impact of shadowing as a learning strategy. We explored students’ perceptions and lived experiences of shadowing to understand its role and impact on their personal and professional lives.Methods: Between 2020-2021, individual semi-structured video interviews were conducted with 15 Canadian medical students in this qualitative descriptive study. Inductive analysis proceeded concurrently with data collection until no new dominant concepts were identified. Data were iteratively coded and grouped into themes.Results: Participants described internal and external factors that moulded shadowing experiences, arising tensions between intended and perceived experiences, and how these lived experiences impacted their wellness. Internal factors associated with shadowing behaviour included: 1) aspiring to be the best and shadowing to demonstrate excellence, 2) shadowing for career exploration, 3) shadowing as learning opportunities for early clinical exposure and career preparedness, and 4) reaffirming and redefining professional identity through shadowing. External factors were: 1) unclear residency match processes which position shadowing as competitive leverage, 2) faculty messaging that perpetuates student confusion around the intended value of shadowing, and 3) social comparison in peer discourse, fuelling a competitive shadowing culture.Conclusions: The tension between balancing wellness with career ambitions and the unintended consequences of unclear messaging regarding shadowing in a competitive medical culture highlights issues inherent in shadowing culture.